THE DIFFERENCE OF WEIGHT GAIN IN 5 CONTRACEPTIVE GROUPS IN PUSKESMAS DUPAK SURABAYA AREA - Nurul Istiqomah; Nila Kurniasari; Budiono Budiono (Indonesian Midwifery and Health Sciences Journal, 2020)
AbstractBackground: Weight gain is one of the predominantly problem for women who’s in childbearing age. Weight gain that occurs at women in childbearing age is often associated with contraceptive use. One type of contraception that affects weight gain is the hormonal contraception. Lerning the weight gain from each use of contraception is important as a consideration for the family planning program. Methods: This research method was observational analytic with cross-sectional design. Sample size was 136 respondents and the sampling technique used total sampling. The independent variable is the type of contraception includes 1 month injection contraception, 3 month injection contraception, implant contraception, combined pill contraception, and copper T. IUD contraception. The dependent variable is the weight gain. Data was analyzed with Kruskal Wallis test. Results: The results showed that 120 respondents from 5 contraceptive groups experienced weight gain after using contraception. The results of the Kruskal Wallis test were obtained at value of P <0.0001 (p <0.05). that there are differencea in weight gain in 5 groups of contraception. Conclusion: there are difference in weight gain from each contraceptive groups and the contraception that most influences weight gain is 3 months injection contraception.